Wound healing activity of the ethanol root extract and polyphenolic rich fraction from Potentilla fulgens - Kundu A.; Ghosh A.; Singh N.K.; Singh G.K.; Seth A.; Maurya S.K.; Hemalatha S.; Laloo D. (My University, 2025)
Context: Potentilla fulgens Wall. ex Hook (Rosaceae) is a potent medicinal plant of the Western Himalayas, where its roots are traditionally used by the local people of Uttaranchal (India) to treat wounds and tiger bites. Objective: The present study scientifically evaluates the wound healing activity of P. fulgens ethanol root extract (EPF) and its ethyl acetate fraction (PFEA) on experimental rats. Materials and methods: Wounds were inflicted on animals by using both excision and incision models. The wounded animals were treated for 16 days with EPF (oral: 200–400 mg/kg and topical: 5–10% w/w) and PFEA (oral: 75 mg/kg; topical: 1.75% w/w). Various physical (wound contraction, epithelialization rate, tensile strength) and biochemical parameters (hydroxyproline, hexosamine, proteins, DNA) were examined during the study. Oxidant product (lipidperoxidase), antioxidant enzymes (catalase, superoxide-dismutase) and reduced glutathione were determined. Morphological and histopathological studies of the skin tissues were monitored. Results: A significant (p < 0.05) wound healing property was observed when the animals were treated topically with EPF (10% w/w) and PFEA (1.75% w/w). A significantly (p < 0.05) increased in the levels of hydroxyproline, hexosamine, protein and DNA up to 59.22, 70.42, 61.01 and 60.00% was observed, respectively. This effect was further demonstrated by the morphological and histopathological representation, thus showing significant (p < 0.05) re-epethelialization on the healing area. EPF and PFEA also showed significant (p < 0.05) antioxidant activity. Conclusions: The present study provided the scientific evidence, where P. fulgens rich in polyphenolic components possess remarkable wound healing activities, thereby supporting the traditional claims. © 2016 Informa UK Limited, trading as Taylor & Francis Group.